Good Policies and Practices on Rural Transport in Africa : Monitoring and Evaluation - Airey, Anthony (World Bank, Washington, DC, 2015)
This publication is part of a series aimed at promoting good policies and practices on rural transport in Africa. A recent review of the status of Rural Transport Knowledge Products and Practice (Riverson, 2012) identified a number of knowledge gaps and recommended the production of working papers to address these. One of these gaps was the absence of robust tools, including relevant indicators and instruments, to measure the impact of rural transport projects on rural growth and poverty reduction. This paper addresses this gap. The focus on impact monitoring appears relatively straightforward but in reality requires a distinction between effects and impact, terms used interchangeably in the literature. Similarly, there is a range of technical terms and definitions applied to Monitoring and Evaluation, presented in annex four. A monitoring and evaluation system is an essential element of planning, design and implementation of a rural transport project1 as it serves to assess whether it has achieved its objective and its development goal. Thus, the Millennium Challenge Corporation (MCC) sees independent evaluations as the most rigorous means of measuring [program] impact and [is] at the heart of MCC s commitment to accountability, learning, transparency, and evidence-based decision-making. Yet, there are few completed independent evaluations on the MCC website and the majority of their evaluation effort seems focused on performance monitoring. Similarly, the Indian Government s results-based management of its large agricultural support program separates outcomes from impact and stresses the importance of the former as a means of assessing the performance of government departments such as public works and transport in supporting the government s ambitious agricultural development program (Government of Kerala Memo, 2013).